2017
DOI: 10.1016/j.comcom.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Efficient content delivery through fountain coding in opportunistic information-centric networks

Abstract: Opportunistic networks can increase network capacity, support collaborative downloading of content and offload traffic from a cellular to a cellular-assisted, device-to-device network. They can also support communication and content exchange when the cellular infrastructure is under severe stress and when the network is down or inaccessible. Fountain coding has been considered as especially suitable for lossy networks, providing reliable multicast transport without requiring feedback from receivers. It is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In the previous section, we have shown that the objective function in the maximization problem in (20) is a monotone non-decreasing submodular function. We can now show that the optimization problem defined by Eqs.…”
Section: Greedy Algorithmsmentioning
confidence: 98%
See 2 more Smart Citations
“…In the previous section, we have shown that the objective function in the maximization problem in (20) is a monotone non-decreasing submodular function. We can now show that the optimization problem defined by Eqs.…”
Section: Greedy Algorithmsmentioning
confidence: 98%
“…It thus holds that ∆D v,t u (S 1 ) ≤ ∆D v,t u (S 2 ), i.e., the distortion reduction at user u for reconstructing the segment B v,t is a monotone non-decreasing function. Hence, the objective function in (20) is also monotone non-decreasing as a linear combination of monotone non-decreasing functions with non-negative weights.…”
Section: Proposition 2 the Objective Function In (20) Is A Monotone mentioning
confidence: 99%
See 1 more Smart Citation
“…Network coding has various theoretical frameworks [11][12][29][30][31]. In this study, we employed an algebraic approach to network coding, as discussed in another study [11].…”
Section: Algebraic Approach To Network Coding For Icnmentioning
confidence: 99%
“…They can also support communication and content exchange when the cellular infrastructure is under severe stress [2][22] [23], whereas at the same time, are the only means of communication when the network infrastructure is down or inaccessible due to natural disasters or government censorship. In opportunistic networks, connectivity among devices is intermittent and communication can be very lossy.…”
Section: Related Workmentioning
confidence: 99%